2019
DOI: 10.1111/nep.13530
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in caregivers compared with dialysis recipients: The Co‐ACTIVE sub‐study of the ACTIVE dialysis trial

Abstract: The authors compared quality of life (QOL) of caregivers of dialysis patients versus that of the patients themselves and found that the former had higher physical and equivalent mental QOL but poorer personal well-being than the Chinese population norm. ABSTRACT:Aim: To compare quality of life (QOL) of caregivers of dialysis patients with the cared for patients and population norms.Methods: The ACTIVE Dialysis study randomized participants to extended (median 24 h/week) or standard (median 12 h/week) haemodial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…We also observed that caregivers of dialysis patients had worse mental health scores compared with the caregivers of conservative care patients indicating poorer mental health. We could not find any studies comparing these two treatment groups specifically, but found previous studies reporting greater impairment to mental health and vitality domains of HRQoL of caregivers of dialysis patients [12,44,45]. In the care-related quality of life, we observed that the domain of 'assistance from organisations and government' received lower scores in both treatment groups compared with other domains.…”
Section: Discussioncontrasting
confidence: 75%
“…We also observed that caregivers of dialysis patients had worse mental health scores compared with the caregivers of conservative care patients indicating poorer mental health. We could not find any studies comparing these two treatment groups specifically, but found previous studies reporting greater impairment to mental health and vitality domains of HRQoL of caregivers of dialysis patients [12,44,45]. In the care-related quality of life, we observed that the domain of 'assistance from organisations and government' received lower scores in both treatment groups compared with other domains.…”
Section: Discussioncontrasting
confidence: 75%
“…Tasks such as taking the patient to the hemodialysis center and staying with them during the process, preparing special foods, and taking patients to their physician’s office prevent family caregivers from taking care of their personal affairs and themselves [ 4 ]. Evidence shows that the caregivers of these patients deal with various problems and disorders, such as stress, depression, anxiety, lack of self-confidence, fatigue, social isolation, financial and communication limitations, poor marital adjustment, and low quality of life and sleep, which can disrupt their physical, social and emotional welfare [ 5 7 ]. The result of a study showed that though caring for hemodialysis patients threatens the caregiver’s psychological integrity, it provides the opportunity of development capabilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies reported that the QOL and mental conditions of patients and their caregivers/families were affected negatively by chronic kidney disease and haemodialysis [ 42 , 43 , 44 ]. Clinically, scores lower than 40 for SF-36v2 are considered to indicate deterioration of QOL compared to the Japanese general population [ 10 , 31 ].…”
Section: Resultsmentioning
confidence: 99%